Chitosan Salts as Stabilizing Agents for the Synthesis of Silver Nanoparticles (AgNPs). Issue 1 (2nd January 2023) - Costa, Marina; Carreiro, Elisabete P.; Filho, Cesar M. C.; Silva, Mara; Gonçalves, Isabel; Souza, Esmar F.; Teixeira, António P. S.; Craveiro, Alexandre; Burke, Anthony J.
Abstract: In this work, silver nanoparticles (AgNPs) were obtained by a chemical reduction method using different chitosan salts as stabilizing agents, able to protect and prevent against the aggregation of the nanoparticles. Various chitosan salts with different organic acids, which included: acetic, succinic, formic, propionic, malic, glycolic and lactic acid were used to form the chitosan salts. The use of these organic acids represents a viable, sustainable, environmentally friendly and economical way to synthesized AgNPs. The AgNPs‐chitosan salts samples were analyzed by UV‐VIS, ATR‐FTIR spectroscopy, DLS, and TEM. Most of the organic acids led to nanoparticles with small dimensions (30–52 nm) and positive zeta‐potential. However, those AgNPs‐chitosan that were stabilized by the salts of α‐hydroxyacids and diacids, like glycolate and succinate, led to larger particles. The stability study under different storage conditions and time showed that the silver nanoparticles are more stable when storage at cold temperatures. Abstract : New sustainable synthetic route for AgNPs using chitosan‐carboxylate salts as stabilizing agents was developed. The size of the AgNPs obtained was less than 100 nm with an almost spherical shape. No aggregation was observed for AgNPs stored in cold when chitosan‐propionate and lactate salts were used for the AgNPs synthesis.